A novel method to achieve the flotation of pyrite from lizardite slime without collector or depressant. (1st October 2020) - Yang, Siyuan; Xu, Yanling; Liu, Cheng; Ai, Guanghua; Huang, Lingyun; Yu, Hong
Graphical abstract: Highlights: The efficient collectorless flotation of pyrite from lizardite slime was achieved. Lizardite slime did not affect the pyrite flotation at pH > 11 in the presence of Na2 S. Lizardite slime detached from pyrite surface due to the electrostatic repulsion. Exposed pyrite surface was beneficial to the adsorption and conversion of Na2 S. Abstract: A combination of sodium sulfide (Na2 S) and pH adjustment was introduced in this study to achieve the efficient flotation of pyrite from lizardite slime. Microflotation results showed that the addition of lizardite slime could depress the floatability of the pyrite but it did not interfere with the pyrite flotation under high alkalinity condition in the presence of Na2 S. Zeta potential measurements revealed that the surface charges of lizardite and pyrite were both negative when pH > 10, causing the detachment of lizardite slime from pyrite surface due to the electrostatic repulsion. Then Na2 S could selectively adsorb onto the exposed pyrite surface in the form of HS − and oxidized to the hydrophobic S 0 through the electrochemical interaction, leading to the improvement of pyrite floatability.